Advertisement Remove all ads

Solve for X : (81)^(3/4) - (1/32)^(-2/5) + X(1/2)^(-1).2^0 = 27 - Mathematics

Sum

Solve for x : `(81)^(3/4) - (1/32)^(-2/5) + x(1/2)^(-1).2^0 = 27`

Advertisement Remove all ads

Solution

`(81)^(3/4) - (1/32)^(-2/5) + x(1/2)^(-1).2^0 = 27`

⇒ `3^(4 xx 3/4) - (2^- 5)^(-2/5) + x(2) = 27`

⇒ `3^3 - 2^2 + 2x = 27`
⇒ 2x + 27 - 4 = 27
⇒ 2x = 4
⇒ x = 2

Concept: Solving Exponential Equations
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 9 ICSE
Chapter 7 Indices (Exponents)
Exercise 7 (B) | Q 14.3 | Page 101
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×